Retrospective Analysis of Quality of Pharmacotherapy for Children with Acute Respiratory Infections on Background of ABC /VEN/ Frequency Analysis Based on Data of Patientsꞌ Medical Histories - Vera Ulanova (Journal of Global Pharma Technology, 2018)
Increase in frequency of acute respiratory viral infection (ARVI) and difficult economic situation in Ukraine require rational use of financial resources to treat this disease in children. Comprehensive analysis on background of additional pharmacoeconomic methods: ABC-, VEN- and frequency analysis based on study of results of 180 children with ARVI - allows to estimate  cost of drugs in hospital of Burin town, Sumy region, Ukraine. It has been found out that part of money turned out to have been used inefficiently for treatment of children with ARVI and pharmacotherapy not always to be in line with government regulations because 16.15 % - 38.69 % of all funds were spent on drugs not included in Clinical Protocols for ARVI and related diseases. That is why there is an opportunity to cut down expenditures spent on unnecessary drugs during treatment period.Keywords: Drugs for treatment of children with acute respiratory viral infections, Clinical and economic analysis.